Efficacy of a triage system to reduce length of hospital stay. (June 2014) - Williams, P.; Csipke, E.; Rose, D.; Koeser, L.; McCrone, P.; Tulloch, A. D.; Salaminios, G.; Wykes, T.; Craig, T.
Abstract : Background: Attempts have been made to improve the efficiency of in-patient acute care. A novel method has been the development of a 'triage system' in which patients are assessed on admission to develop plans for discharge or transfer to an in-patient ward. Aims: To compare a triage admission system with a traditional system. Method: Length of stay and readmission data for all admissions in a 1-year period between the two systems were compared using the participating trust's anonymised records. Results: Despite reduced length of stay on the actual triage ward, the average length of stay was not reduced and the triage system did not lead to a greater number of readmissions. There was no significant difference in costs between the two systems. Conclusions: Based on our findings we cannot conclude that the triage system reduced length of stay, but we can conclude that it does not increase the number of readmissions as some have feared.